Permeability of Neotropical agricultural lands to a key native ungulate—Are well-connected forests important? - Jorge, Maria Luisa S. P.; Bradham, Jennifer L.; Keuroghlian, Alexine; Oshima, Júlia Emi F. [UNESP]; Ribeiro, Milton Cezar [UNESP] (Wiley, 2021)
Much of what remains of the Earth's tropical forests is embedded within agricultural landscapes, where forest is reduced and fragmented. As native forest ungulates are critical to maintaining forest function, it is imperative to understand how this functional group responds to declines in forest cover and connectivity resulting from agricultural expansion. We addressed this issue by evaluating selection of forest cover and forest connectivity by a key native ungulate of Neotropical forests, the white-lipped peccary (Tayassu pecari Link 1795, Tayassuidae, Cetartiodactyla), in agricultural landscapes of Brazil. We evaluated selection using compositional analysis at two hierarchical levels, landscape, and home range. From 2013 to 2019, we GPS-tracked eight white-lipped peccary herds in Southwest Brazil, resulting in a total of 14,460 GPS locations. We found that herds can live in landscapes with a wide range of forest cover (35%–81% of home ranges covered by native forest), with significant, but not strong, selection at the landscape level (p =.045). Nevertheless, herds strongly select for forest cover within their home ranges (81%–97% of locations within native forest; highly significant selection at the home-range level: p =.008). As for connectivity, herds significantly select the largest, most connected forest fragments at the landscape level (p =.04), but not at the home-range level (p =.07). Our results support that Neotropical forests within agricultural landscapes need to be well connected in order to preserve this key native ungulate and maintain long-term forest function. Abstract in Portuguese is available with online material.
Keywords: Brazilian Cerrado; functional connectivity; landscape ecology; movement ecology; white-lipped peccaries